Artificial Intelligence and E-commerce Logistics Management towards Operational Excellence - Thakre, Bharat (International Journal of Supply Chain Management, 2025)
The world of trade and commerce has undergone a sea change over the last 2-3 decades with the marvelous development in technology which has revolutionized communication and has brought artificial intelligence (AI) into our world. AI has made our lives easier in several ways and its impact on buyers’ behavior is not far to seek. From the retailers’ perspective, happy customers are satisfied customers who would help to not only maintain the business but also in its expansion. Using AI to achieve operational excellence especially from the perspective of logistics management, an e-retailer can achieve competitive edge that will help it stay ahead of peers. This article shows that AI plays a crucial role in achieving operational excellence in e-commerce, especially from the perspective of Quick Commerce (QC), through efficient management of delivery logistics.